Development of MEHARUN Game Media "Looking for Treasure" Flora and Fauna Distribution Material for Elementary School Students - A’yunin, Maulidiana; Khotimah, Khusnul; Putra, Arda Purnama (Proceedings Series of Educational Studies, 2024)
Based on preliminary data collection at SDN Lecari, SDN Kalirejo 1, and SDN Kalirejo 2, learning media is needed for elementary school students to support teaching and learning activities, especially for social studies subjects. This research was conducted to develop educational game media MEHARUN "Look for Treasure" on Android-based flora and fauna distribution material. This type of development research uses the R&D method using the ADDIE model. The Meharun educational game validation by media experts resulted in a validity level of 95.31% with a very valid category. And the validation test by material experts obtained a validity level of 96.87% with a very valid category. The practicality test aimed at teachers as users obtained a practicality level of 100%. The practicality test in the small group and large group trials had an average of 99.4%. The results of the practicality test are included in the very practical category so that MEHARUN educational game media can be used in social studies learning in grade V elementary school. Keywords: educational game; flora and fauna distribution; elementary school